2011
DOI: 10.1186/cc10073
|View full text |Cite
|
Sign up to set email alerts
|

Virus-associated hemophagocytic syndrome as a major contributor to death in patients with 2009 influenza A (H1N1) infection

Abstract: IntroductionVirus-associated hemophagocytic syndrome (VAHS) is a severe complication of various viral infections often resulting in multiorgan failure and death. The purpose of this study was to describe baseline characteristics, development of VAHS, related treatments and associated mortality rate of consecutive critically ill patients with confirmed 2009 influenza A (H1N1) infection and respiratory failure.MethodsWe conducted a prospective observational study of 25 critically ill patients with 2009 influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 32 publications
6
75
1
3
Order By: Relevance
“…This is thought to be related with cell migration from the circulation to the infected respiratory mucosa during infection (25). It has been reported that hemaphagocytosis, which develops during influenza infection, causes reduction in bone marrow cell series (26). In our study, the most commonly observed abnormal laboratory findings included leukopenia and thrombocytopenia, in accordance with the literature.…”
Section: Discussionsupporting
confidence: 79%
“…This is thought to be related with cell migration from the circulation to the infected respiratory mucosa during infection (25). It has been reported that hemaphagocytosis, which develops during influenza infection, causes reduction in bone marrow cell series (26). In our study, the most commonly observed abnormal laboratory findings included leukopenia and thrombocytopenia, in accordance with the literature.…”
Section: Discussionsupporting
confidence: 79%
“…In the only prospective observational study that has been done in patients with VAHS secondary to influenza A H1N1 infection [14], 9 out of 25 critically ill patients with influenza infection presented hemophagocytic syndrome. The median age of these 9 patients was 53 years (39 to 56), 7 were male, and 5 patients (56%) had an underlying comorbid condition associated with a severe course of illness.…”
Section: Resultsmentioning
confidence: 99%
“…Only English language papers were reviewed. This search revealed 15 other cases of adults with influenza A associated HPS [5][6][7][8][9][10][11][12][13] and a prospective observational study carried out in 25 critically ill patients with VAHS secondary to influenza H1N1 which was not included in the analysis because of incomplete individual patient data [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations